Middle school - Safe rafe! - Patterson, James 1947-; Tebbetts, Chris (Patterson, James Middle school, 2014)
"Middle schooler Rafe Khachadorian faces his greatest challenge yet as he struggles to complete a week-long wilderness survival course to prove to his school administrators that he can succeed"..